Special makeup effects for stage and screen : making and applying prosthetics - Debreceni, Todd (Routledge, Taylor & Francis Group, 2019)
"With this new edition of Special Makeup Effects for Stage and Screen, author Todd Debreceni presents the latest techniques and special effects in what has become an industry "bible." In addition to genre-specific considerations, Debreceni covers the latest gear you will need and details how to maintain your kit, how to take care of the actor's skin, how to airbrush for HD, and much more. With in-depth, step-by-step tutorials, learn how to sculpt and mold your own makeup prosthetics, focusing on human anatomy to create the most realistic effects. This new and expanded edition features updated information on lifecasting, prosthetics made using 3D printing, advanced airbrushing techniques, new artist profiles, and includes updated images and illustrations throughout. A companion website contains artist profiles that showcase some of the world's top makeup effects artists, including Steve Wang, Ve Neill, Matthew W. Mungle, Miles Teves, Jordu Schell, and many others. Also included are detailed makeup tutorials led by experts in the field, such as Maddie Singer and Toby Sells"--